Geologic hazard risk assessment of slopeland villages in Southern Taiwan using remote sensing techniques - Shu, Rong Yang; Yi, Lung Yeh (Universiti Kebangsaan Malaysia, 2015)
Countering the dangers associated the present extreme climate not only requires continuous improvement of local disaster prevention engineering infrastructure but also needs an enhanced understanding of the causes of the disasters. This study investigates the geologic hazard risk of 53 slopeland villages in Pingtung county of southern Taiwan. First, remote sensing (RS) techniques were utilized to interpret environmental geology and geologic hazard zonation, including dip slope, fault, landslide and debris flow. GIS map overlay analysis was used to further identify the extent of the geologic hazard zonation. As a final step, field investigation is used to comprehend geologic, topographic conditions and the geologic hazard risk specific to each locality. Based on data analysis and field investigation results, this study successfully integrates RS, GIS and GPS techniques to construct a geologic hazard risk assessment method of slopeland village. The results of this study can be used to promote support for future disaster prevention and disaster mitigation efforts.